Join the conversation on IDNLearn.com and get the answers you seek from experts. Ask anything and get well-informed, reliable answers from our knowledgeable community members.

Someone please help!
Write the function h(x) = -5 (x - 1)^2 + 3 in standard form. ​


Sagot :

Answer:

[tex]h(x)=-5x^2+10x-2[/tex]

Step-by-step explanation:

[tex]h(x) = -5 (x - 1)^2 + 3\\\\\implies h(x) = -5 (x - 1)^2 + 3\\\\\implies h(x)=-5(x^2-2x+1)+3\\\\\implies h(x) = -5x^2+10x-5+3\\\\\implies h(x)=-5x^2+10x-2[/tex]